Chemical Synthesis of Polycarbazole (PCz), modification and pH sensor application - Gupta B.; Prakash R.; Melvin A. (My University, 2025)
Synthesis of Polycarbazole (PCz) is reported using anhydrous ferric chloride as an oxidizing agents. A comparative study of chemically synthesized PCz with electrochemically synthesized is also made. A composite of PCz and polyvinyl chloride (PVC) containing 20% PVC by weight is synthesized and used for the development of solid state pH electrode. The composite was synthesized to improve mechanical strength, stability, and restrict solubility. The pH sensor response is found to be reversible and linear in the pH range 5-10 with sensitivity 35±2mV/pH. PCz and PVC (20 wt%) based pH sensors show potential applications in development of pH transducers based sensors/biosensors. © 2012 IEEE.